My Heart is Aflame: Exploring Three Dimensions of the Poet's Voice in Selected Stanzas - Salma Deria Putri; R. Myrna Nur Sakinah (Faculty of Ushuluddin, Adab, and Humanities Universitas Islam Negeri Salatiga, 2025)
My Heart is Aflame by Al-Mutanabbi is a lengthy poem that intricately weaves personal emotion, panegyric praise, and rhetorical self-pride. This study aims to examine three dimensions of the poet’s voice in selected stanzas, employing a stylistic approach that focuses on diction, imagery, figurative language, and concrete words. The analysis reveals that Al-Mutanabbi consistently constructs a complex lyrical persona: a wounded lover suffering from unrequited affection, an admirer exalting the figure of Saif al-Dawlah in heroic terms, and an individual proudly affirming his prowess as both poet and warrior. Through the use of intense word choices and rich figurative and imagistic elements, the poem conveys the poet’s identity as a grand figure within the cultural and literary tradition of classical Arabic society. This analysis highlights Al-Mutanabbi’s expressive strength in blending personal sentiment with elevated linguistic strategies, making his poetry a vehicle of self-assertion and cultural positioning.